Monoallelic mutations in SLCO2A1 cause autosomal dominant primary hypertrophic osteoarthropathy. (5th May 2021) - Xu, Yang; Zhang, Zeng; Yue, Hua; Li, Shanshan; Zhang, Zhenlin
ABSTRACT: Primary hypertrophic osteoarthropathy (PHO) is a rare disease inherited as a recessive or irregular dominant trait and characterized by digital clubbing, pachydermia, and periostosis. Biallelic mutations in HPGD and SLCO2A1, disturbing prostaglandin E2 (PGE2 ) catabolism and leading to increased circulating PGE2 level, cause PHO autosomal recessive 1 (PHOAR1) and PHO autosomal recessive 2 (PHOAR2), respectively. However, no causative genes have been reported for PHO autosomal dominant (PHOAD). Here, we performed Sanger sequencing and whole‐genome sequencing (WGS) on DNA samples from seven Chinese PHOAD families; after excluding other single‐nucleotide variants (SNVs), structural variations (SVs), and copy number variations (CNVs) in the genomes, we reported six SLCO2A1 monoallelic mutations (c.1660G>A [p.G554R], c.664G>A [p.G222R], c.1106G>A [p.G369D], c.1065dupA [p.Q356TfsX77], c.1293delT [p.S432AfsX48], and c.1807C>T [p.R603X]) in the probands and affected family members. Then, in five other PHO families with probands carrying SLCO2A1 biallelic mutations, we verified that parents with SLCO2A1 monoallelic mutations also displayed PHO manifestations, which further confirmed the pathogenicity of SLCO2A1 monoallelic mutations and illustrated the allelic nature of PHOAD and PHOAR2. Subsequently, through comparison of seven PHOAD probands and 50 PHOAR2 patients, we found onset age in puberty and skewed penetrance rate were similar in both PHO types, but symptoms and signs of PHOAD were milder, including less severe pachydermia ( p = .027) and periostosis ( p = .005), and less frequent cutis verticis gyrata ( p = .011), acne ( p = .005), arthralgia ( p = .037), and anemia ( p = .023). The median urinary PGE2 level in PHOAD probands was almost half that in PHOAR2 patients (PHOAD 277.58 ng/mmoL creatinine, PHOAR2 473.19 ng/mmoL creatinine; p = .038). Moreover, through the 3‐month trial of oral administration of etoricoxib, an effective response similar to that we reported previously in PHOAR2 patients was observed in PHOAD probands. In conclusion, our findings confirm that SLCO2A1 monoallelic mutations are the cause of PHOAD and broaden phenotypic spectrum of PHO. © 2021 American Society for Bone and Mineral Research (ASBMR).